Performance management systems at Ghana Water Company Limited, Northwest II - Accra - Ayerakwa, Enoch (My University, 2015)
ABSTRACT It is estimated that 50% of the water produced by GWCL is lost before the water gets to the consumer. The sight of leakages, unaccounted for water and the unchanged colonial water supply systems still in use in some districts in Accra, the capital of Ghana, served as a motivation for this research. The main questions raised revolve around the current Performance Management System (PMS) and the factors affecting the performance of Ghana Water Company Limited (GWCL) at the North West II District (a sub-metropolis of Accra North), which was chosen as the study focus. The introduction of Performance Management Systems (PMS) in the public sector of developing nations was meant to reform weak administrative systems; however the success rate is still below average. This study sought to explore the factors leading to the poor performance of the Performance Management System in the Ghana Water Company Limited (GWCL), specifically in North West II District. A qualitative research approach was employed. Respondents for this study were mainly senior management officials of the District. The study established that, although the benefits of an effective Performance Management System is extensively known by managers and other professionals, however its implementation is constrained by several internal and external factors. Internal factors such as: how management perceives PMS, lack of human capital, weak systems of measuring performances, and external factors that include:Information Communication and Technology (ICT), Power Outages, Government and the traditional Culture, were identified as the main challenging factors. In addition, this study recommended topics of intervention such as, Capacity development and the implementation of a PMS, incentives as a motivator for excellent performers and traditional culture, to improve the current state of Performance at the District level.
MM 2014
Keywords: Performance Management, Public administration, Water resources development.